Energy consumption optimization of central air-conditioning based on sequential-least-square-programming - Xie, Jupeng; Zhang, Huajun; Shen, Yu; Li, Mengchuan (Chinese Control and Decision Conference, 2020)
In order to solve the problem of high energy consumption in central air-conditioning, the sequential-least-square-programming is adopted to optimize the energy consumption of central air-conditioning model. By using DOE-2 model and regression method, the mathematical model of each component of the central air-conditioning system is obtained. The energy consumption optimization problem is reduced to a constrained nonlinear programming problem. According to the basic principle of nonlinear programming, the objective function and constraint conditions of total energy consumption are obtained. Finally, the program of calculating the operating parameters of the optimal energy consumption point is designed by using the sequential-least-square-programming algorithm.